Soft carbon coated sulfur-nitrogen co-doped coal-based hard carbon material and preparation method thereof

Through sulfur-nitrogen co-doping and soft carbon coating technology, the sodium storage performance and first-time Coulomb efficiency of coal-based hard carbon materials are improved, solving the problem of poor sodium storage performance of existing materials in sodium ion batteries.

CN119560543APending Publication Date: 2025-03-04SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411840906.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing coal-based hard carbon materials have poor sodium storage performance in sodium ion batteries, and the first Coulomb efficiency is low, affecting the battery's energy storage and release capabilities.

Method used

By mixing bituminous coal and thiourea to co-carbonize, sulfur-nitrogen co-doped hard carbon material is prepared, and asphalt is deposited on its surface, and secondary carbonization is carried out to form a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material.

Benefits of technology

The proportion of sodium storage capacity and platform area specific capacity of the material has been improved, and the first Coulomb efficiency has been improved to reach 70%~75%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a soft carbon coated sulfur-nitrogen co-doped coal-based hard carbon material and a preparation method thereof.The preparation method comprises the steps that firstly, bituminous coal powder and thiourea particles are dissolved in absolute ethyl alcohol, fully stirred and mixed to be uniform, and after drying, bituminous coal-thiourea mixed powder is prepared; carrying out primary carbonization treatment on the bituminous coal-thiourea mixed powder in an inert atmosphere to prepare a sulfur-nitrogen co-doped coal-based hard carbon material; and depositing asphalt on the surface of the sulfur and nitrogen co-doped coal-based hard carbon material, and carrying out secondary carbonization treatment on the product to prepare the soft carbon coated sulfur and nitrogen co-doped coal-based hard carbon material, a sodium ion battery based on the soft carbon coated sulfur-nitrogen co-doped coal-based hard carbon material has high sodium storage specific capacity and first coulombic efficiency and high potential platform area sodium storage capacity proportion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery electrode materials and relates to a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have many advantages such as low cost, good safety performance, and low-temperature retention performance. They are used for large-scale energy storage to support the rapid development of clean energy and can provide strong support for achieving the era goal of "carbon peak and carbon neutrality". At present, high-performance, low-cost negative electrode materials are one of the bottlenecks restricting the practical application of sodium-ion batteries. Hard carbon materials have a non-graphitizable amorphous structure, mainly composed of curved and irregularly distributed graphene nanosheets. Their carbon microcrystals are small in size and large in interlayer spacing, which can achieve the storage of more sodium ions. They are sodium-ion battery negative electrode materials with good commercial prospects.

[0003] Coal resources are considered to be a promising carbon negative electrode precursor because of their abundant reserves and high carbon abundance, showing outstanding cost advantages. However, coal-based hard carbon currently has problems such as low specific capacity and low first coulombic efficiency, which are not conducive to the commercial application of materials. In this regard, the introduction of functional sites or groups by heteroatom doping can help improve the electronic structure, microchemical environment and surface properties of carbon materials, thereby improving sodium storage performance. Ye et al. (Journal of Power Sources, 2019, 412:606-614) prepared sulfur-nitrogen co-doped mesoporous carbon by one-step heat treatment. At 0.1 A g -1 A current density of 419 mAh g was achieved. -1 The reversible specific capacity of hard carbon materials is 26.1%, but the initial coulombic efficiency is only 26.1%. Synergistic doping is a better choice to improve the sodium storage specific capacity of hard carbon materials, but heteroatom doping leads to increased surface defects and more side reactions between the electrolyte and the electrode surface, which causes the material to show a low initial coulombic efficiency during the sodium storage process, affecting the overall energy storage and release capacity of the battery. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and a preparation method thereof, thereby solving the technical problem of poor sodium storage performance of coal-based hard carbon materials in the prior art.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material comprises the following steps: S1: dissolving bituminous coal powder and thiourea particles in anhydrous ethanol, stirring and mixing them evenly, and drying them to obtain a bituminous coal-thiourea mixed powder; S2: subjecting the bituminous coal-thiourea mixed powder to a carbonization treatment under an inert atmosphere to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and performing a secondary carbonization treatment on the product to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material.

[0006] Preferably, the bituminous coal powder is pretreated before being mixed with the thiourea particles, and the pretreatment process is as follows: the raw coal is crushed and sieved; then the sieved bituminous coal powder is immersed in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifugally filtered until the pH value of the supernatant is 7, and after sufficient drying, the pretreated bituminous coal powder is obtained.

[0007] Preferably, after the sieving process, a bituminous coal powder having an average particle size of 38 to 75 μm is obtained.

[0008] Preferably, in step S1, the mass ratio of thiourea to bituminous coal is (0.5-4):1.

[0009] Preferably, in step S2, during the carbonization treatment, the temperature is 700-1500°C, the heating rate is 2-10°C / min, and the insulation time is 1-4 h.

[0010] Preferably, in step S3, the mass ratio of the asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is (2-8):0.25; the deposition temperature is 300-600°C, and the deposition time is 2-10 h.

[0011] Preferably, in step S4, during the secondary carbonization treatment, the temperature is 900-1300° C. and the time is 1-4 h.

[0012] A soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material is prepared by the above method; the interior of the hard carbon material is carbon microcrystals with a sulfur-nitrogen co-doped structure, and the surface is coated with a soft carbon layer; the carbon interlayer spacing of the carbon microcrystals is 0.365-0.405 nm; the carbon interlayer spacing of the soft carbon layer is 0.351-0.358 nm, and the overall specific surface area of ​​the material is 1.75-5.35 m 2 g -1 , the pore volume is 0.0053 cm 3 g -1 ~0.0302 nm.

[0013] A negative electrode material comprises the above-mentioned soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material.

[0014] A sodium ion battery, comprising the above-mentioned negative electrode material; the reversible specific capacity of the sodium ion battery is 300-360 mAh g -1 The first coulombic efficiency is 70%~75%, and the capacity below 0.1 V is 150~230mAh g -1。

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The sulfur-nitrogen co-doped hard carbon material is obtained by mixing bituminous coal with an external sulfur source and co-carbonizing. The carbon microcrystalline structure inside the material has a large carbon layer spacing, which is conducive to the embedding of sodium ions, and is conducive to increasing the intercalation sodium storage capacity and obtaining a higher platform area capacity. Then, by utilizing the polynuclear aromatic compounds volatilized by high-temperature cracking of asphalt to be deposited on the surface of the hard carbon material, on the one hand, it is conducive to inducing the pores in the hard carbon to be closed and form closed pores, which can effectively increase the filling sodium storage capacity and further increase the platform area capacity ratio; on the other hand, with the help of the high conductivity and less surface defects of the soft carbon coating produced by deposition, the side reactions of the electrode material and the electrolyte can be effectively alleviated, and finally a coal-based hard carbon negative electrode material with high sodium storage specific capacity, high platform area specific capacity ratio and high first coulomb efficiency is obtained. The raw material used in the present invention is bituminous coal with a moderate degree of metamorphism. The raw material is widely available, cheap and conducive to the high-value utilization of bituminous coal. The present invention combines sulfur-nitrogen heteroatom co-doping and soft carbon coating modification to develop a hard carbon material with rich internal pore structure, large carbon layer spacing, many active sites, few external defect structures, and good electrical conductivity, so that it can achieve high sodium storage capacity while having high first coulomb efficiency, which is for coal-based hard carbon negative electrode materials. In the present invention, the sulfur-nitrogen co-doping strategy of using coal as raw material and carbonizing it with sulfur source and nitrogen source is used to achieve the regulation of carbon microcrystals in hard carbon, increase the carbon layer spacing, and improve the material intercalation sodium storage capacity; further, combined with the soft carbon coating strategy of asphalt vaporization and cracking deposition on the surface of doped hard carbon, on the one hand, the open pores generated in the doping activation process are induced to close to form a closed-pore structure, thereby improving the material's filling and sodium storage capacity; on the other hand, the soft carbon coating can reduce the surface defects of the material and improve the first coulomb efficiency of the material in the sodium storage process.

[0016] Furthermore, the bituminous coal powder is pretreated before being mixed with the thiourea particles, and the pretreatment process is as follows: the raw coal is crushed and sieved; the sieved bituminous coal powder is then immersed in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifuged and filtered until the pH value of the supernatant is 7. After sufficient drying, the pretreated bituminous coal powder is obtained, which can remove electrochemically inert silicates and other minerals in the bituminous coal and increase the proportion of carbon components in the electrode.

[0017] Furthermore, after the screening process, a bituminous coal powder with an average particle size of 38-75 μm is obtained, which can be heated evenly in the subsequent carbonization process, thereby improving the uniformity of the hard carbon material particles.

[0018] Furthermore, in step S1, the mass ratio of thiourea to bituminous coal is (0.5-4):1, which can efficiently realize a series of coal-based hard carbon material precursors with uniform sulfur / nitrogen atom doping.

[0019] Furthermore, in step S2, during the carbonization treatment, the temperature is 700~1500 ℃, the heating rate is 2~10 ℃ / min, and the insulation time is 1~4 h, so that a series of sulfur-nitrogen co-doped hard carbon materials with different carbonization degrees can be obtained, which are used to construct the relationship between the doped hard carbon structure and the sodium storage performance, so as to improve the sodium storage capacity of coal-based hard carbon materials.

[0020] Furthermore, in step S3, the mass ratio of the asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is (2~8):0.25; the deposition temperature is 300~600°C, and the deposition time is 2~10 h, which can make the asphalt thermal cracking volatiles fully and relatively evenly deposited on the surface of the hard carbon particles to construct closed pores, so as to further improve the platform area sodium storage capacity of the coal-based hard carbon material during the charging and discharging process.

[0021] Furthermore, in step S4, during the secondary carbonization treatment, the temperature is 900~1300°C and the time is 1~4h, which can cause the asphalt thermal cracking volatiles deposited on the hard carbon surface to rearrange and form a soft carbon coating with a high degree of graphitization, so as to improve the first coulomb efficiency of the coal-based hard carbon material in the sodium storage process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 1 with a mass ratio of 1:1 (thiourea to bituminous coal) as described in Example 1 and a bitumen addition amount of 2 g; Figure 2 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 2 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 2 and a bitumen addition amount of 2 g; Figure 3The transmission electron microscope image of the bituminous coal-based hard carbon material sample 2 of the second deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 2, and the amount of asphalt added is 2 g; Figure 4 The high-resolution transmission electron microscope image of the bituminous coal-based hard carbon material sample 2 of the secondary deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 2, and the amount of asphalt added is 2 g; Figure 5 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 3 of secondary deposition carbonization is 4:1 (mass ratio of thiourea to bituminous coal) as described in Example 3, and the amount of asphalt added is 2 g; Figure 6 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 4 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 4 and a bitumen addition amount of 0 g; Figure 7 The transmission electron microscope image of the bituminous coal-based hard carbon material sample 4 of the second deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 4, and the amount of asphalt added is 0 g; Figure 8 The high-resolution transmission electron microscope image of the bituminous coal-based hard carbon material sample 4 of the secondary deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 4, and the amount of asphalt added is 0 g; Fig. 9 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 5 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 5 and a bitumen addition amount of 5 g; Fig.10 The transmission electron microscope image of the bituminous coal-based hard carbon material sample 5 of the second deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 5, and the amount of asphalt added is 5 g; Fig.11 The high-resolution transmission electron microscope image of the bituminous coal-based hard carbon material sample 5 of the secondary deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 5, and the amount of asphalt added is 5 g; Fig.12 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 6 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 6 and an amount of asphalt added of 8 g; Fig.13 The transmission electron microscope image of the bituminous coal-based hard carbon material sample 6 of the secondary deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 6, and the amount of asphalt added is 8 g; Fig.14The high-resolution transmission electron microscope image of the bituminous coal-based hard carbon material sample 6 of the secondary deposition carbonization is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 6, and the amount of asphalt added is 8 g; Fig.15 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 7 of secondary deposition carbonization with a mass ratio of 0:1 (thiourea to bituminous coal) as described in Comparative Example 1 and an amount of asphalt added of 2 g; Fig.16 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 8 without secondary deposition carbonization treatment with asphalt, which is 0:1 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 2; Fig.17 This is a high-resolution transmission electron microscope image of a bituminous coal-based hard carbon material sample 8 without secondary deposition carbonization treatment with pitch, which is 0:1 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 2; Fig.18 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 9 without secondary deposition carbonization treatment with asphalt, which is 1:2 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 3; Fig.19 This is a high-resolution transmission electron microscope image of a bituminous coal-based hard carbon material sample 9 without secondary deposition carbonization treatment with pitch, which is 1:2 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 3; Fig. 20 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 10 described in Comparative Example 4, which is 1:1 (mass ratio of thiourea to bituminous coal) and has not been subjected to secondary deposition carbonization treatment with asphalt; Fig.21 This is a high-resolution transmission electron microscope image of a bituminous coal-based hard carbon material sample 10 without secondary deposition carbonization treatment with pitch as described in Comparative Example 4, which has a ratio of 1:1 (thiourea to bituminous coal by mass); Fig. 22 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 11 without secondary deposition carbonization treatment with asphalt, which is 2:1 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 5; Fig.23 This is a high-resolution transmission electron microscope image of a bituminous coal-based hard carbon material sample 11 without secondary deposition carbonization treatment with pitch, which is 2:1 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 5; Fig.24 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 12 without secondary deposition carbonization treatment with asphalt described in Example 6, which is 4:1 (mass ratio of thiourea to bituminous coal); Fig.25 This is a high-resolution transmission electron microscope image of a bituminous coal-based hard carbon material sample 12 having a 4:1 (mass ratio of thiourea to bituminous coal) ratio as described in Example 6, without secondary deposition carbonization treatment with asphalt.

[0024] Fig.26 The specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 2 of secondary deposition carbonization with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 2 and an asphalt addition amount of 2 g.

[0025] Fig. 27 The specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 4 which is 2:1 (mass ratio of thiourea to bituminous coal) as described in Example 4, with the amount of asphalt added being 0 g.

[0026] Fig.28 This is a specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 7 that was carbonized by secondary deposition at a ratio of 0:1 (mass ratio of thiourea to bituminous coal) as described in Comparative Example 1, with an asphalt addition amount of 2 g.

[0027] Fig.29 This is a specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 8 of 0:1 (mass ratio of thiourea to bituminous coal) described in Example 2 without secondary deposition carbonization treatment with asphalt.

[0028] Fig.30 This is a specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 10 of 1:1 (mass ratio of thiourea to bituminous coal) described in Example 4 without secondary deposition carbonization treatment with asphalt.

[0029] Fig.31 This is a specific surface area and pore size analysis diagram of the bituminous coal-based hard carbon material sample 11 of 2:1 (mass ratio of thiourea to bituminous coal) described in Example 5, without secondary deposition carbonization treatment with asphalt. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0032] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0033] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0034] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0035] The present invention provides a method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material, comprising the following steps: S1: crushing and sieving the raw coal to obtain bituminous coal powder with an average particle size of 38-75 μm, then immersing the sieved bituminous coal powder in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifugally filtering until the pH value of the supernatant is 7, and fully drying to obtain the pretreated bituminous coal powder; dissolving the bituminous coal powder and thiourea particles in anhydrous ethanol at a mass ratio of (0.5-4):1, stirring and mixing well, and then placing in a blast drying oven, keeping warm at 60°C for 2h to dry, to obtain a bituminous coal-thiourea mixed powder; The raw coal is a type of bituminous coal. The concentration of hydrochloric acid in the mixed acid solution of hydrochloric acid and hydrofluoric acid is 1-4 mol / L, and the concentration of hydrofluoric acid is 10-40 wt%.

[0036] S2: The bituminous coal-thiourea mixed powder is subjected to a carbonization treatment at 700-1500°C and a heating rate of 2-10°C / min under an inert atmosphere for 1-4 hours, washed with dilute hydrochloric acid and water until the supernatant is neutral, and then dried to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; The inert atmosphere is argon gas, and of course the inert atmosphere can also be replaced by nitrogen gas.

[0037] S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and subjecting the product to secondary carbonization treatment to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The mass ratio of asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is (2-8):0.25; the deposition temperature is 300-600 °C, and the deposition time is 2-10 h; during the secondary carbonization treatment, the temperature is 900-1300 °C, and the time is 1-4 h. The asphalt is medium-temperature asphalt.

[0038] The above-mentioned asphalt is deposited on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and the product is subjected to secondary carbonization treatment. The specific process is: the asphalt is placed at the air inlet end in the heating zone of the tubular furnace, and the sulfur-nitrogen co-doped coal-based hard carbon is placed at the exhaust port end in the heating zone of the tubular furnace for secondary carbonization to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The surface of the hard carbon material is modified by soft carbon coating, and the interior is modified by sulfur and nitrogen heteroatom doping.

[0039] The present invention adopts the internal modification strategy of heteroatom doping to optimize the electronic structure and expand the carbon layer spacing for coal-based hard carbon, and the external modification strategy of soft carbon coating to reduce surface defects, construct closed pores and improve the conductivity of the material. The two strategies are reasonably combined to obtain a sodium ion battery hard carbon negative electrode material with higher sodium storage capacity and high first coulomb efficiency. The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material of the present invention uses bituminous coal after impurity removal and purification as the carbon source, thiourea as the dopant, and then mixed under high temperature conditions of 700~1500℃ to achieve nitrogen and sulfur atom doping to obtain sulfur-nitrogen co-doped hard carbon; medium-temperature asphalt is used as the deposition source, and is cracked into small molecular structures under 300~600℃ conditions, and is deposited on the surface of sulfur-nitrogen co-doped hard carbon located at the exhaust port section from the air inlet end with inert gas, and then cyclized and aromatized under high temperature conditions of 900~1300℃, finally obtaining the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material.

[0040] The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material of the present invention has a uniform soft carbon coating layer on the surface, a large carbon layer spacing inside, and a hard carbon core with rich nanopore structure. It can be applied to the negative electrode material of sodium ion batteries to achieve high sodium storage capacity, large platform area capacity ratio and high first coulomb efficiency. The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0042] Example 1 (1) Grinding: crush the bituminous coal raw materials in sequence to obtain fine coal powder, and control the particle size of the coal powder to be less than 200 mesh; (2) impurity removal and drying: the sieved coal powder in step (1) is acid-washed with a mixed solution of hydrochloric acid (4 mol / L) and hydrofluoric acid (10 wt%), stirred at a constant temperature of 25 °C for 12 h, and then washed with water by centrifugation and suction filtration until neutral to obtain a washed product, which is then dried; (3) Mixing: Dissolve the purified coal powder and thiourea in deionized water at a mass ratio of 1:1, stir and mix thoroughly, and dry; (4) Heat treatment: The material dried in step (3) is subjected to a high temperature heat treatment at 1100°C for 2 h at a heating rate of 5°C / min in an inert atmosphere, and then naturally cooled to room temperature to obtain sulfur-nitrogen co-doped hard carbon.

[0043] (5) Deposition heat treatment: 2 g of asphalt was placed at the air inlet end of a tubular furnace, and 0.25 g of sulfur-nitrogen co-doped hard carbon after doping in step (4) was placed at the exhaust end. The temperature was increased to 400 °C at a rate of 5 °C / min in an inert atmosphere and kept at this temperature for 3 h. The temperature was increased to 1100 °C at a rate of 5 °C / min and kept at this temperature for 2 h. The temperature was naturally cooled to room temperature to obtain the finished product, i.e., the hard carbon negative electrode material, i.e., the sulfur-nitrogen co-doped coal-based hard carbon material coated with soft carbon. The sample was marked as sample 1.

[0044] The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material prepared in this embodiment is used as the negative electrode of the sodium ion battery and an electrochemical charge and discharge test is carried out. The hard carbon material, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive agent (Super P) prepared in this embodiment are weighed in a mass ratio of 8:0.5:0.5:1, and the corresponding four materials are first mixed evenly in an agate mortar, and then deionized water is added dropwise with a solid-liquid mass ratio of 1:3, and stirred thoroughly. Then the stirred slurry is evenly coated on a copper foil with a thickness of about 20 μm, and the coated copper foil is transferred to a vacuum drying oven and dried at 90°C for 12 hours. After it is fully dried, the dried diaphragm is punched into a circular electrode using a special mold.

[0045] The punched electrode sheet and the metal sodium counter electrode were assembled into a CR2032 button cell. The entire battery assembly process was completed in an ultra-clean glove box filled with argon. After the battery assembly was completed, the assembled battery was taken out of the glove box and sealed on a sealing machine. After standing for 12 hours, the battery was sealed at 0.03 A g -1 The constant current charge and discharge performance was tested at a current density of .

[0046] Example 2 The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and the electrochemical charge-discharge test were prepared according to the method of Example 1, except that the mass ratio of thiourea to coal powder in step (3) was 2:1. The final coal-based hard carbon material was marked as Sample 2.

[0047] Example 3 The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and the electrochemical charge-discharge test were prepared according to the method of Example 1, except that the mass ratio of thiourea to coal powder in step (3) was 4:1. The final coal-based hard carbon material was marked as Sample 3.

[0048] Example 4 The sulfur-nitrogen co-doped coal-based hard carbon material was prepared and electrochemical charge-discharge tested according to the method of Example 2, except that the mass of asphalt added in step (5) was 0 g. The coal-based hard carbon material finally obtained was a sulfur-nitrogen co-doped coal-based hard carbon material, marked as Sample 4.

[0049] Example 5 The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and the electrochemical charge-discharge test were prepared according to the method of Example 2, except that the mass of asphalt added in step (5) was 5 g. The final coal-based hard carbon material was marked as Sample 5.

[0050] Example 6 The soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material and the electrochemical charge-discharge test were prepared according to the method of Example 2, except that the mass of asphalt added in step (5) was 8 g. The final coal-based hard carbon material was marked as Sample 6.

[0051] Comparative Example 1 A soft carbon-coated coal-based hard carbon material was prepared and electrochemical charge and discharge tests were performed according to the method of Example 1, except that the mass of thiourea added in step (3) was 0 g. The final coal-based hard carbon material obtained was a soft carbon-coated coal-based hard carbon material, which was marked as Sample 7.

[0052] Comparative Example 2 A sulfur-doped coal-based hard carbon material was prepared and electrochemical charge-discharge tests were performed according to the method of Comparative Example 1, except that the heat treatment in step (5) was not performed. The final coal-based hard carbon material obtained was a soft carbon-coated coal-based hard carbon material, marked as Sample 8.

[0053] Comparative Example 3 The sulfur-doped coal-based hard carbon material was prepared and electrochemical charge-discharged tested according to the method of Comparative Example 2, except that the mass ratio of thiourea to coal powder in step (3) was 1:2. The final coal-based hard carbon material was marked as Sample 9.

[0054] Comparative Example 4 A sulfur-doped coal-based hard carbon material was prepared and subjected to electrochemical charge and discharge tests according to the method of Comparative Example 2, except that the mass ratio of thiourea to coal powder in step (3) was 1:1. The final coal-based hard carbon material was labeled as Sample 10.

[0055] Comparative Example 5 A sulfur-doped coal-based hard carbon material was prepared and subjected to electrochemical charge and discharge tests according to the method of Comparative Example 2, except that the mass ratio of thiourea to coal powder in step (3) was 2:1. The final coal-based hard carbon material was labeled as Sample 11.

[0056] Comparative Example 6 The sulfur-doped coal-based hard carbon material was prepared and electrochemical charge-discharged tested according to the method of Comparative Example 2, except that the mass ratio of thiourea to coal powder in step (3) was 4:1. The final coal-based hard carbon material was marked as Sample 12.

[0057] Figure 1 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 1 with a mass ratio of 1:1 (thiourea to bituminous coal) as described in Example 1 and an amount of asphalt added of 2 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 79.8%, and the reversible specific capacity is 277.1 mA hg -1 .

[0058] Figure 2 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 2 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 2 and a bituminous coal-based hard carbon material sample 2 with a mass ratio of 2 g is shown in the figure. The first coulomb efficiency is 74.6% and the reversible specific capacity is 360.1 mA hg -1 .

[0059] Figure 5 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 3 with a mass ratio of 4:1 (thiourea to bituminous coal) as described in Example 3 and an amount of asphalt added of 2 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 66.8%, and the reversible specific capacity is 235.5 mA hg -1 .

[0060] Figure 6 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 4 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 4 and an amount of asphalt added of 0 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 60.4%, and the reversible specific capacity is 207.6 mA hg -1 .

[0061] Fig. 9 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 5 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 5 and an amount of asphalt added of 5 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 73.7% and the reversible specific capacity is 337.6 mA hg -1 .

[0062] Fig.12The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 6 with a mass ratio of 2:1 (thiourea to bituminous coal) as described in Example 6 and an amount of asphalt added of 8 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 71.8%, and the reversible specific capacity is 320.6 mA hg -1 .

[0063] Fig.15 The constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 7 with a mass ratio of 0:1 (thiourea to bituminous coal) as described in Example 1 and an amount of asphalt added of 2 g is shown in the figure. As can be seen from the figure, the first coulomb efficiency is 80.0%, and the reversible specific capacity is 202.6 mA hg -1 .

[0064] Fig.16 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 8 without secondary deposition carbonization treatment with asphalt, which is 0:1 (mass ratio of thiourea to bituminous coal) described in Example 2. As can be seen from the figure, the first coulomb efficiency is 61.7%, and the reversible specific capacity is 252.8 mA hg -1 .

[0065] Fig.18 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 9 without secondary deposition carbonization treatment with asphalt, which is 1:2 (mass ratio of thiourea to bituminous coal) described in Example 3. As can be seen from the figure, the first coulomb efficiency is 65.9%, and the reversible specific capacity is 305.4 mA hg -1 .

[0066] Fig. 20 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 10 without secondary deposition carbonization treatment with asphalt described in Example 4. As can be seen from the figure, the first coulomb efficiency is 62.6%, and the reversible specific capacity is 349.8 mA hg -1 .

[0067] Fig. 22 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 11 without secondary deposition carbonization treatment with asphalt described in Example 5 (2:1) (mass ratio of thiourea to bituminous coal). It can be seen from the figure that the first coulomb efficiency is 54.3%, and the reversible specific capacity is 201.6 mA hg -1 .

[0068] Fig.24 This is the constant current charge-discharge curve of the bituminous coal-based hard carbon material sample 12 without secondary deposition carbonization treatment with asphalt described in Example 6. It can be seen from the figure that the first coulomb efficiency is 27.3%, and the reversible specific capacity is 96.3 mA hg -1 .

[0069] Figure 3 , Figure 7 , Fig.10 and Fig.13 Transmission electron microscope images of asphalt deposition source addition amounts of 2 g, 0 g, 5 g and 8 g are given respectively. By comparison, it can be found that a uniform carbon coating layer can be formed on the surface of doped hard carbon after carbonization after high-temperature cracking and deposition of asphalt, and the thickness of the coating layer increases with the increase of asphalt source addition amount.

[0070] Figure 4 , Figure 8 , Fig.11 and Fig.14 High-resolution transmission electron microscopy images of asphalt deposition source with addition amounts of 2 g, 0 g, 5 g and 8 g were given respectively, and the carbon layer spacing was analyzed. The carbon layer spacing of the coating layer was small and the carbon layers were uniform and continuous, showing the characteristics of soft carbon. The carbon layer spacing inside the particles was large and the carbon layers were chaotically interlaced, showing the characteristics of hard carbon.

[0071] Fig.17 , Fig.19 , Fig.21 , Fig.23 and Fig.25 High-resolution transmission electron microscopy images of bituminous coal-based hard carbon with carbonization ratios of 0:1, 1:2, 1:1, 2:1 and 4:1 of thiourea and bituminous coal without secondary asphalt deposition carbonization process are given respectively. The carbon layer spacing increases with the increase of doping ratio, accompanied by the generation of a large number of nanopores.

[0072] Fig.26 , Fig. 27 , Fig.28 , Fig.29 , Fig.30 and Fig.31 The specific surface area and pore size analysis data of samples 2, 4, 7, 8, 10 and 11 are given respectively. It can be seen from the figure that sulfur-nitrogen co-doping modification can increase the specific surface area and pore volume of the material, while secondary carbonization has relatively little effect on the specific surface area and pore volume of the material. The decrease in the specific surface area of ​​the material after asphalt deposition can indirectly prove that the open pores in the material are transformed into closed pores.

[0073] Table 1 Constant current charge and discharge test results of the above embodiments and comparative examples

[0074] From the results in Table 1, it can be seen that compared with the hard carbon negative electrode material of sample 7 which has not been subjected to heteroatom doping treatment, the hard carbon negative electrode material of sample 2 under the optimal ratio condition of the present invention has a conductivity of 360.1 mA hg -1Compared with the hard carbon negative electrode materials of samples 8 to 12 that have not been subjected to secondary asphalt-based soft carbon deposition carbonization treatment, the hard carbon negative electrode material of sample 2 of the present invention has a higher first coulombic efficiency of 74.6% and a high specific capacity of 226 mA h g -1 The larger platform area sodium storage capacity below 0.1V is beneficial to the positive and negative electrode matching application of sodium ion batteries.

[0075] Table 2 Summary of specific surface area and pore size analysis of some examples and comparative examples

[0076] It can be seen from the results in Table 2 that compared with the hard carbon negative electrode material of sample 7 which has not been doped with heteroatom, the hard carbon materials of samples 10 and 11 of the present invention have larger specific surface area and pore volume after doping, while the hard carbon material of sample 2 deposited after doping has relatively smaller specific surface area and pore volume than before deposition. Compared with the hard carbon material of sample 4 obtained by adding 0 g asphalt under the same heating conditions, it can be shown that the secondary carbonization treatment has little effect on the specific surface area of ​​the material, and the reduction in specific surface area and pore size is due to the closure of open pores.

[0077] Example 7 A method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material comprises the following steps: S1: crushing and sieving the raw coal to obtain bituminous coal powder with an average particle size of 75 μm, then immersing the sieved bituminous coal powder in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifugally filtering until the pH value of the supernatant is 7, and fully drying to obtain the pretreated bituminous coal powder; dissolving the bituminous coal powder and thiourea particles in anhydrous ethanol at a mass ratio of 0.5:1, fully stirring and mixing, and slowly drying to obtain a bituminous coal-thiourea mixed powder; The raw coal is a kind of bituminous coal. The concentration of hydrochloric acid in the mixed acid solution of hydrochloric acid and hydrofluoric acid is 1 mol / L, and the concentration of hydrofluoric acid is 10 wt%.

[0078] S2: The bituminous coal-thiourea mixed powder is subjected to a carbonization treatment at 700°C and a heating rate of 2°C / min in an argon atmosphere for 4 hours, washed with dilute hydrochloric acid and water until the supernatant is neutral, and then dried to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and subjecting the product to secondary carbonization treatment to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The mass ratio of asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is 2:0.25; the deposition temperature is 300 °C, and the deposition time is 10 h; during the secondary carbonization treatment, the temperature is 900 °C and the time is 4 h.

[0079] Example 8 A method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material comprises the following steps: S1: crushing and sieving the raw coal to obtain bituminous coal powder with an average particle size of 38 μm, then immersing the sieved bituminous coal powder in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifugally filtering until the pH value of the supernatant is 7, and fully drying to obtain the pretreated bituminous coal powder; dissolving the bituminous coal powder and thiourea particles in anhydrous ethanol at a mass ratio of 4:1, fully stirring and mixing, and slowly drying to obtain a bituminous coal-thiourea mixed powder; The raw coal is a type of bituminous coal. The concentration of hydrochloric acid in the mixed acid solution of hydrochloric acid and hydrofluoric acid is 4 mol / L, and the concentration of hydrofluoric acid is 40 wt%.

[0080] S2: The bituminous coal-thiourea mixed powder is subjected to a carbonization treatment at 1500°C and a heating rate of 10°C / min in a nitrogen atmosphere for 1 h, washed with dilute hydrochloric acid and water until the supernatant is neutral, and then dried to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and subjecting the product to secondary carbonization treatment to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The mass ratio of asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is 8:0.25; the deposition temperature is 600 °C, and the deposition time is 2 h; during the secondary carbonization treatment, the temperature is 1300 °C and the time is 1 h.

[0081] Example 9 A method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material comprises the following steps: S1: crushing and sieving the raw coal to obtain bituminous coal powder with an average particle size of 50 μm, then immersing the sieved bituminous coal powder in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifugally filtering until the pH value of the supernatant is 7, and fully drying to obtain the pretreated bituminous coal powder; dissolving the bituminous coal powder and thiourea particles in anhydrous ethanol at a mass ratio of 2:1, fully stirring and mixing, and slowly drying to obtain a bituminous coal-thiourea mixed powder; The raw coal is a kind of bituminous coal. The concentration of hydrochloric acid in the mixed acid solution of hydrochloric acid and hydrofluoric acid is 2 mol / L, and the concentration of hydrofluoric acid is 30 wt%.

[0082] S2: The bituminous coal-thiourea mixed powder is subjected to a carbonization treatment at 1000°C and a heating rate of 5°C / min in an argon atmosphere for 2 hours, washed with dilute hydrochloric acid and water until the supernatant is neutral, and then dried to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and subjecting the product to secondary carbonization treatment to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material. The mass ratio of asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is 5:0.25; the deposition temperature is 400 °C, and the deposition time is 8 h; during the secondary carbonization treatment, the temperature is 1000 °C and the time is 2 h.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Various changes, modifications, substitutions and variations made to these embodiments should all be included in the protection scope of the present invention.

Claims

1. A method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material, characterized in that: The following steps are involved: S1: dissolving bituminous coal powder and thiourea particles in anhydrous ethanol, stirring and mixing them evenly, and drying them to obtain a bituminous coal-thiourea mixed powder; S2: subjecting the bituminous coal-thiourea mixed powder to a carbonization treatment under an inert atmosphere to obtain a sulfur-nitrogen co-doped coal-based hard carbon material; S3: Depositing asphalt on the surface of the sulfur-nitrogen co-doped coal-based hard carbon material, and performing a secondary carbonization treatment on the product to obtain the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material.

2. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 1, characterized in that: The bituminous coal powder is pretreated before being mixed with the thiourea particles. The pretreatment process is as follows: the raw coal is crushed and sieved; the sieved bituminous coal powder is then immersed in a mixed acid solution of hydrochloric acid and hydrofluoric acid for purification, and centrifuged and filtered until the pH value of the supernatant is 7. After being fully dried, the pretreated bituminous coal powder is obtained.

3. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 2, characterized in that: After the sieving process, bituminous coal powder with an average particle size of 38-75 μm is obtained.

4. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 1, characterized in that: In step S1, the mass ratio of thiourea to bituminous coal is (0.5-4):

1.

5. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 1, characterized in that: In step S2, during the carbonization treatment, the temperature is 700-1500°C, the heating rate is 2-10°C / min, and the insulation time is 1-4 h.

6. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 1, characterized in that: In step S3, the mass ratio of the asphalt to the sulfur-nitrogen co-doped coal-based hard carbon material is (2-8):0.25; the deposition temperature is 300-600°C, and the deposition time is 2-10 h.

7. The method for preparing a soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material according to claim 1, characterized in that: In step S4, during the secondary carbonization process, the temperature is 900-1300°C and the time is 1-4 hours.

8. A soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material, characterized in that: The hard carbon material is prepared by the method described in any one of claims 1 to 7; the interior of the hard carbon material is carbon microcrystals with a sulfur-nitrogen co-doped structure, and the surface is covered with a soft carbon layer; the carbon interlayer spacing of the carbon microcrystals is 0.365-0.405 nm; the carbon interlayer spacing of the soft carbon layer is 0.351-0.358 nm, and the overall specific surface area of ​​the material is 1.75-5.35 m 2 g -1 , the pore volume is 0.0053 cm 3 g -1 ~0.0302 nm.

9. A negative electrode material, characterized in that: The invention comprises the soft carbon-coated sulfur-nitrogen co-doped coal-based hard carbon material as claimed in claim 8.

10. A sodium ion battery, characterized in that: The invention comprises a negative electrode material as claimed in claim 9; the reversible specific capacity of the sodium ion battery is 300-360 mAh g -1 The first coulombic efficiency is 70%~75%, and the capacity below 0.1 V is 150~230mAh g -1 .

Citation Information

Patent Citations

  • Composite hard carbon material and preparation method and application thereof

    CN115911320A

  • Nitrogen-doped coal-based hard carbon material, preparation method and application thereof, and secondary battery

    CN116443850A